(untitled) (Journal on Excellence in College Teaching, 2024)
A collaborative course introduced history students to a variety of digital tools and printed materials for historical research. The authors explore the development of this program by a historian and a librarian as a case study to address the value of teaching history outside of the classroom and allowing students to conduct research on-site. This type of research allows students to "do history" and identify how to critically read an archival document or a manuscript and how to understand the importance of libraries, archival institutions, and historical documents in a historical framework. The authors examine the purpose of the course and assess the impact on the cohort of students.